Application of CRISPR/Cas9-Based Gene Editing in HIV-1/AIDS Therapy - Xiao, Qiaoqiao; Guo, Deyin; Chen, Shuliang (Frontiers in Cellular and Infection Microbiology, 2019)
Despite the fact that great efforts have been made in the prevention and resistance of HIV-1 infection, HIV-1/AIDS remains a major threat to global human health. Highly active antiretroviral therapy (HAART) can suppress virus replication, but it cannot eradicate latent viral reservoirs in HIV-1/AIDS patients. Recently, the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated nuclease 9 (Cas9) system has been engineered as an effective gene-editing technology with the potential to treat HIV-1/AIDS. It can be used to target cellular co-factors or HIV-1 genome to reduce HIV-1 infection and clear the provirus, as well as to induce transcriptional activation of latent virus in latent viral reservoirs for elimination. This versatile gene editing technology has been successfully applied to HIV-1/AIDS prevention and reduction in human cells and animal models. Here, we update the rapid progress of CRISPR/Cas9-based HIV-1/AIDS therapy research in recent years and discuss the limitations and future perspectives of its application.